IMPLIKASI KEBIJAKAN INVESTASI ASING DALAM UU CIPTA KERJA TERHADAP UMKM - Djauzie, Muhamad Zaky (Honeste Vivere, 2024)
This research aims to analyze the implications of investment in the Omnibus law Undang-Undang Cipta Kerja on the competition of micro, small, and medium enterprises (UMKM) sector in Indonesia. The method used is a literature study by collecting data from various reliable sources. The results show that the Omnibus law Undang-Undang Cipta Kerja has significant implications for business and investment in Indonesia, including for the UMKM sector. The law aims to create a quality business and investment climate for businesses, including UMKM and foreign investors. However, some critics argue that the law may lead to a concentration of economic power in the hands of large corporations and reduce opportunities for small and medium-sized businesses. The implications of investment in the Omnibus law Undang-Undang Cipta Kerja need to be carefully considered to ensure that the UMKM sector can compete fairly and sustainably in an increasingly competitive market.